Shifting the cantus firmus: Australian music educators and the ERA - Bennett, Dawn (Australian Society for Music Education, 2010)
Managing the teaching-research-creative practice nexus is a concern for everyone working in higher music education, particularly those involved with the supervision and mentorship of graduate students and early career academics. This paper takes as its subject the new Excellence in Research for Australia (ERA), drawing examples from research frameworks elsewhere to identify some of the pertinent issues facing music educators and their students. The findings from a series of surveys and short interviews suggest that the formal recognition of artistic research remains largely dependent on the articulation of that research into traditional academic language. Furthermore, the increasing focus on research as a form of revenue generation highlights the separation of research and teaching and the lessening of academic autonomy. The paper argues that a balance can be achieved only with a fundamental, systemic shift that recognises the new knowledge and innovative methodological approaches within artistic research and, equally, within the scholarship of teaching.